Redesain Remote Laboratorium Rumpun Mata Kuliah Jaringan Komputer FTI UKDW dengan Pendekatan Modular - Narung, Olivia; Indriyanta, Gani; Raharjo, Willy Sudiarto (Fakultas Teknologi Informasi, 2024)
The implementation of a remotely accessible network laboratory at FTI UKDW commenced in 2022, utilizing a VPN (Virtual Private Network) based remote system. Previous research identified several technical challenges in its implementation, coupled with periodic subscription cost constraints. Consequently, this study aims to redesign the system by adopting port forwarding as an alternative, with the expectation of optimizing the remote laboratory implementation while reducing maintenance costs. This research focuses on analyzing the performance quality of the redesigned remote laboratory using the port forwarding method. Additionally, the study aims to measure the level of comfort among students in using the remote network laboratory system through the collection of questionnaire data. The results of the research indicate that the redesign with the port forwarding method can be implemented as expected. Students expressed a high level of satisfaction, reaching 50%, with the majority finding it easy to access practical tools and considering the system user-friendly.